2015
DOI: 10.13177/irpa.a.2015.11.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Individualistic Vikings: Culture, Economics and Iceland

Abstract: Icelandic culture has generally been considered to share many similarities to the Nordic cultures. However, the financial crisis in 2008 painted a completely different picture, with the Nordic nations faring much less worse than Iceland, which saw its banking system becoming almost entirely worthless. Looking at traditional cultural yardsticks in the vein of the most commonly used research in the field of business and organizational management, generally linked to Hofstede´s dimensional studies, one would at f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…Brett Vigelska, the CEO of Costco in Iceland, said in an interview that the Costco store in Iceland was a little bigger than a regular Costco store and more American in its design, because they wanted to respond positively to that Icelanders seemed to have affection for what was American and wanted to respond to that (Mbl.is 2017). This is in line with previous studies in Iceland (Aðalsteinsson, Guðmundsdóttir & Guðlaugsson 2011;Mixa & Vaiman 2015;Ólafsson 2003) It is interesting that, in the light of this, the Costco store in Iceland is mainly controlled via Britain. A few days before the opening, the possible gas price also leaked out -intentionally or not -when a photo was circulated on the web showing the gas price on one of the pumps (Daða-son 2017a).…”
Section: The Opening Of Costcosupporting
confidence: 91%
“…Brett Vigelska, the CEO of Costco in Iceland, said in an interview that the Costco store in Iceland was a little bigger than a regular Costco store and more American in its design, because they wanted to respond positively to that Icelanders seemed to have affection for what was American and wanted to respond to that (Mbl.is 2017). This is in line with previous studies in Iceland (Aðalsteinsson, Guðmundsdóttir & Guðlaugsson 2011;Mixa & Vaiman 2015;Ólafsson 2003) It is interesting that, in the light of this, the Costco store in Iceland is mainly controlled via Britain. A few days before the opening, the possible gas price also leaked out -intentionally or not -when a photo was circulated on the web showing the gas price on one of the pumps (Daða-son 2017a).…”
Section: The Opening Of Costcosupporting
confidence: 91%
“…Consequently, individuals with a value-oriented approach to individualism and competition enter Iceland's higher education system. Secondly, the business and management field in Iceland somewhat different than in other Nordic countries (Mixa &Vaiman, 2015). More specifically, Mixa and Vaiman (2015) propose that, in terms of individualism, as defined by Hofstede's dimensions, that Icelandic managers are more individualistic than managers in other Nordic countries.…”
Section: The Current Studymentioning
confidence: 98%
“…Secondly, the business and management field in Iceland somewhat different than in other Nordic countries (Mixa &Vaiman, 2015). More specifically, Mixa and Vaiman (2015) propose that, in terms of individualism, as defined by Hofstede's dimensions, that Icelandic managers are more individualistic than managers in other Nordic countries. Furthermore, it is suggested that when the individualism dimension is considered in management settings, Icelanders are more similar to other nations with the highest scores in the world, such as the United States, the Netherlands, Australia, Sweden, and the United Kingdom.…”
Section: The Current Studymentioning
confidence: 98%
See 1 more Smart Citation
“…Skýr merki voru um meiri áhaettusaekni Íslendinga en t.d. nágranna þeirra annars staðar á Norðurlöndum á bóluárunum (Mixa og Vaiman, 2015).…”
Section: A Brief Stay In Purgatory? Management In Iceland Before and unclassified